2016
DOI: 10.1007/s00392-016-1008-7
|View full text |Cite
|
Sign up to set email alerts
|

First clinical experience using a novel high-resolution electroanatomical mapping system for left atrial ablation procedures

Abstract: The present study is the largest to describe experience of LA ablation procedures using Rhythmia. PVI was achieved in all patients. Applying this ultra high-resolution electroanatomical mapping system under routine conditions leads to a high level of confidence. More data will be mandatory before final conclusions can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Fluoroscopy during radiofrequency ablation (RFA) of supraventricular tachycardia (SVT) exposes patients and operators to ionizing radiation. The demand for reducing radiation exposure by optimizing fluoroscopy or by the use of advanced technologies during these procedures is particularly important [14]. Previous reports have shown that the aim of zero-fluoroscopy during conventional ablation procedures can be reached [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoroscopy during radiofrequency ablation (RFA) of supraventricular tachycardia (SVT) exposes patients and operators to ionizing radiation. The demand for reducing radiation exposure by optimizing fluoroscopy or by the use of advanced technologies during these procedures is particularly important [14]. Previous reports have shown that the aim of zero-fluoroscopy during conventional ablation procedures can be reached [5].…”
Section: Introductionmentioning
confidence: 99%
“…One patient ablated in the anterior sinus experienced recurrence at the 1‐month follow‐up with a VAs configuration change. The remaining patients did not experience a recurrence during the mean 7‐month follow‐up.…”
Section: Resultsmentioning
confidence: 95%
“…IntellaMap Orion (Boston Scientific, Marlborough, MA) is a mini‐basket array catheter with 64 flat mini‐electrodes (0.4 mm 2 , 2.5 mm center‐to‐center interelectrode space). Combined with the Rhythmia mapping system (Boston Scientific), ultra‐high density and resolution electroanatomic maps could be obtained rapidly and automatically . In this study, we mapped RVOT‐type VAs using the Orion catheter and Rhythmia mapping system to exploit the electrophysiological characteristics of the earliest activation of RVOT VAs under ultra‐high density and resolution mapping using mini‐electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The Rhythmia Mapping System has already been successfully used in various types of arrhythmias, including atrial tachycardia, atrial fibrillation, atrioventricular nodal re-entry tachycardia, ventricular tachycardia in structural heart disease or in the healthy heart (7)(8)(9)(10)(11)(12)(13)(14)(15) . The principal part of the mapping system is a 8.5 F basket mapping catheter (Intelamap Orion, Boston Scientific), introduced into the target chamber.…”
Section: Discussionmentioning
confidence: 99%